Criminological Aspects of Current Cyber Security - Vilks, Andrejs; Kipane, Aldona; Kudeikina, Inga; Palkova, Karina; Grasis, Janis (Law, State and Telecommunications Review, 2022)
[Purpose] To analyze the criminological features of the sensitivity of security in the cyber space on the basis of theoretical and empirical bases. [Methodology] In order to evaluate the criminological aspects of the phenomenon under study, theoretical guidelines, special literature, opinions of national and foreign specialists, research papers and periodicals are analyzed. The following scientific research methods have been used in the development of the study: content analysis, analytical, inductive and deductive approaches, as well as systematic analysis of documents, generalization and forecasting. [Findings] The authors conclude that the cyber culture and behaviour of the society need to be improved. This would reduce the potential harm of an individual’s interests and would raise an individual’s understanding of cyber hygiene. An important direction of victimological prevention of cybercrime is a set of systematic and targeted measures to inform people on behaviour of a potential criminal, identifying him/her and personal protective measures and methods to avoid becoming a victim of cyber violations. [Practical Implications] The materials of the article are of practical value for teachers engaged in the development of lectures, seminars, assignments for independent work.